Detection of LBW Newborn by Measuring Chest Circumference - Uddin, Mohammed Jamal; Hoque, Md Mahbubul; Nazia, Sahifa; Chowdhury, Abu Sayeed; Khanam, Morsheda (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Birth weight is the most sensitive and reliable indicator of child survival and the health of the community. Anthropometric measurements have been proposed as surrogate for birth-weight. These include the chest, head and mid upper arm circumferences of the newborn. In most studies done so far chest circumference has the highest sensitivity followed by head circumference, mid upper arm circumference (MUAC) and foot length to identify LBW newborn . Chest and Head circumference is used to identify LBW newborn in developing country. Objectives: Detection of LBW newborn by measuring chest circumference. Methods: Two hundred term and preterm newborns were taken. All measurements were taken within 0-48 hours of delivery. Babies were weighed naked by electronic weighing scale (Tronix pediatrics weighing scale- 4800) to the nearest 20 gm. Chest circumference were measured at the level of nipple at the end phase of expiration with the help of a flexible non-stretchable tape to the nearest of 0.1 cm. The best cutoff point of chest circumference for detecting low-birth-weight <30.5 cm at low risk (who are low birth weight) and lower cut-off points of <29.5 cm at higher risk (who are very low birth weight) were taken as working definition. Results: This study showed the prevalence of low birth-weight was 65% and the mean birth weight was 2478±700 gm. This study also showed that 39.5% percent were term babies. Chest circumference has significant correlation with birth weight (r-0.765). It is also observed that newborns with chest circumference <30.5 cm the chance of low birth weight is 96.2% and when chest circumference will be >30.5 cm 92.6% of them will not be low birth weight. Conclusion: This study showed that in absence of a weighing scale, simple measurement like chest circumference may be the best indicator to identify newborns with low birth weight (<2500 gm). Chest circumference has significant correlation with birth weight and it is an indicator to identify LBW neonates. DS (Child) H J 2019; 35(1) : 22-26